Laminate composites with enhanced pyroelectric effects for energy harvesting - Chang, Harrison Hoon Seok; Huang, Zhaorong (Institute of Physics (IOP), 2010)
A pyroelectric coefficient enhanced 2-2 connectivity laminate composites' energy harvesting credentials have been assessed. The use of the electrothermal coupling factor for laminate composites (k(Lam)(2)) for such an assessment has been appraised while the experimental samples are evaluated to show a significant improvement in their performance via pyroelectric coefficient enhancement, demonstrative of their great potential in energy harvesting applications. A lead zirconate titanate and stainless steel laminate composite with an 88% pyroelectric coefficient enhancement is shown to increase its maximum power density, efficiency, and electrothermal coupling factor by 254%, while other material pairings have also been evaluated to exhibit great promise in this application owing to a large pyroelectric coefficient enhancement accompanied by a reduction in total thermal mass.
Keywords: piezoelectric constants conversion optimization temperature efficiency crystals device